The Effect of Governance Quality and Earning Management With Internal Control as Moderating Variable Towards Firm Value - Mufidah Mufidah; Ira Febrianti; Masnun Masnun (DINASTI RESEARCH, 2020)
The purpose of this study is to analyze the influence of the quality of corporate governance, real earnings management on firm value and to analyze the influence of the quality of corporate governance with the internal control system as a moderating variable on firm value in companies included in the LQ 45 index 2016-2018. The data in this study used descriptive statistical analysis and inferential statistical analysis. The results showed that the Quality of Governance had no significant effect on Firm Value, Earnings Management had a significant effect on Firm Value and Internal Control could not moderate the effect of Governance Quality on Firm Value.